The teaching of medical nosography coordinated with clinical and therapeutic medical - Delgado Cornejo, César (1956)
We must first of all do a little souvenir of how courses and Medical Clinic Medical Nosography were carried in the Dos de Mayo Hospital before the year 1939 Nosography The students who were in the 4th year and is dictated Clinic was studied in the 6th year of medicine; these courses were run by professors Drs. Sergio E. Bernales and Max Gonzales Olaechea respectively.